Work stress and occupational burnout among dental staff in a medical center - Chen-Yi Lee; Ju-Hui Wu; Je-Kang Du (Elsevier, 2019)
Background/purpose: Research on work stress and occupational burnout among Taiwanese dental staff is scarce. Thus, this study aimed to explore work stress and occupational burnout among dental staff in a medical center. Materials and methods: This study is a cross-sectional survey that included the dental staff of a medical center in Taiwan. They were asked to complete self-reported questionnaires anonymously. The Questionnaire on Medical Workers' Stress (QMWS) was used to assess work stress, and the Maslach Burnout Inventory-Human Service Survey (MBI-HSS) was used to evaluate occupational burnout. In total, 108 valid questionnaires were collected, with a response rate of 79.9%. Data were analyzed using independent t-tests, one-way analysis of variance, Pearson's correlation, and stepwise linear regression. Results: Overall QMWS score indicated that visiting staff perceived significantly higher stress than post-graduate year residents. Average scores of MBI-HSS showed dental assistants' scores as similar to those of high burnout groups; visiting staff and moderate burnout groups had similar scores. Stepwise regression analyses revealed that the significant predictor of emotional exhaustion was the QMWS score, of depersonalization were working as a dental assistant and QMWS score, and of personal accomplishment was holding a teaching position. Conclusion: Work stress and occupational burnout were common among dental staff; this may affect patient safety and should be valued. A stress management program is recommended to promote mental health of dental staff, along with adjustment of working environment, performance evaluation, and promotion systems. Keywords: Burnout, Stress, Dentist, Dental assistant, Medical center